Global modelling studies of hydrogen and its isotopomers using STOCHEM-CRI: Likely radiative forcing consequences of a future hydrogen economy. (18th March 2020) - Derwent, Richard G.; Stevenson, David S.; Utembe, Steven R.; Jenkin, Michael E.; Khan, Anwar H.; Shallcross, Dudley E.
Abstract: A global chemistry-transport model has been employed to describe the global sources and sinks of hydrogen (H2 ) and its isotopomer (HD). The model is able to satisfactorily describe the observed tropospheric distributions of H2 and HD and deliver budgets and turnovers which agree with literature studies. We than go on to quantify the methane and ozone responses to emission pulses of hydrogen and their likely radiative forcing consequences. These radiative forcing consequences have been expressed on a 1 Tg basis and integrated over a hundred-year time horizon. When compared to the consequences of a 1 Tg emission pulse of carbon dioxide, 1 Tg of hydrogen causes 5 ± 1 times as much time-integrated radiative forcing over a hundred-year time horizon. That is to say, hydrogen has a global warming potential (GWP) of 5 ± 1 over a hundred-year time horizon. The global warming consequences of a hydrogen-based low-carbon energy system therefore depend critically on the hydrogen leakage rate. If the leakage of hydrogen from all stages in the production, distribution, storage and utilisation of hydrogen is efficiently curtailed, then hydrogen-based energy systems appear to be an attractive proposition in providing a future replacement for fossil-fuel based energy systems. Highlights: Atmospheric hydrogen has been modelled with a global chemistry-transport model. Increased atmospheric hydrogen could cause increased man-made global warming. Hydrogen has a global warming potential of 5 ± 1 over a 100-year time horizon. Leakage from any future hydrogen energy system must be carefully controlled.